REVIEW : PEMANFAATAN TEKNOLOGI GREENHOUSE DAN HIDROPONIK SEBAGAI SOLUSI MENGHADAPI PERUBAHAN IKLIM DALAM BUDIDAYA TANAMAN HORTIKULTURA - Edi Tando (Universitas Tribhuwana Tunggadewi, 2019)
Horticulture plant is essential component of agricultural development. It brings benefits products horticulture meet their food needs , aesthetic and to maintain health and environment. Climate change and the limited resources land causing loss for farmers food crops and horticulture. The purpose of drafting this paper is to inform the utilization of technology greenhouse and hydroponics as solutions to deal with climate change in the cultivation of plants horticulture. To get the result harvest season which is satisfying in the cultivation of plants horticulture , need to pay attention to environmental factor growing plants. The utilization of greenhouse in the cultivation of plants is one of a manner to give the environment that were more accessible for the condition of optimum position for the growth of plants. The use of hydroponics in cultivation crop can be implemented in greenhouse to keep the growth of plants optimally and protected from outside influences